Pelaksanaan Pemberian Bantuan Hukum Berdasarkan Undang-Undang Nomor 16 Tahun 2011 tentang Bantuan Hukum terhadap Tahanan di Lembaga Pemasyarakatan Kelas IIB Solok - M. Fariz Alfiyan; Yulfa Mulyeni; Eri Arianto (AHKAM, 2026)
The fulfillment of the right to legal aid for detainees in correctional institutions remains uneven, particularly among detainees with limited economic resources, legal knowledge, and access to information. This study aims to analyze the implementation of legal aid provision for detainees at the Class IIB Solok Correctional Institution based on Law Number 16 of 2011 concerning Legal Aid and to identify obstacles in its implementation. This study used a qualitative approach with an empirical legal research design. The research informants consisted of correctional institution officers, detainees, and advocates from Posbakumadin Kota Solok and Posbakumadin Koto Baru, who were selected purposively. Data were collected through interviews and literature study and were then analyzed using qualitative descriptive analysis. The results show that legal aid has been implemented through the stages of socialization, data collection, application submission, verification, advocate appointment, assistance, and reporting. However, its implementation still faces several obstacles, including detainees’ low legal literacy, stigma toward free legal aid services, administrative barriers, delays in assistance, limited advocate schedules, and weak interinstitutional coordination. The conclusion of this study emphasizes that the effectiveness of legal aid provision for detainees depends heavily on strengthening socialization, simplifying administration, ensuring timely assistance, and improving interinstitutional coordination. These findings imply the need for more responsive governance of legal aid services to ensure access to justice for detainees.